VARIATIONS IN THE ICE COVER OF THE ARCTIC BASIN IN THE 21ST CENTURY BASED ON MODEL SIMULATIONS: ESTIMATES OF THE PERSPECTIVES OF THE NORTHERN SEA ROUTE - Mokhov I.I.; Khon V.C.; Roeckner E. (My University, 2007)
Trends in variations of the ice cover of the Arctic Basin were analyzed based on the daily data of simulations for the 21st century to estimate possible perspectives of the Northern Sea Route. Numerical simulations using the coupled atmosphere–ocean general circulation model (AOGCM) ECHAM5/MPI-OM were used in the analysis under a sufficiently aggressive SRES-A2 scenario of anthropogenic emission of greenhouse gases into the atmosphere.